Reduction of magnetic field level in residential old buildings from overhead power lines by means of active screening - Kuznetsov, B. I.; Nikitina, T. B.; Bovdui, I. V.; Kolomiets, V. V.; Kobylianskiy, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2021)
Reduction of the magnetic field induction to the level of modern sanitary standards by means of active screening in residentialn old buildings which are located near existing typical overhead power lines are considered. Active shielding of the magnetic field inside a single-storey and multi-storey building is considered. During the design the number, configurations, spatial arrangement of the shielding windings, as well as the currents in the shielding windings were determined. Methodology. The design problem for the system of active shielding reduced to solving the minimax vector optimization problem. The vector of objective function in this minimax problem is calculated based on Biot-Savart's law. The solution of this problem is based on multi-agent optimizationn algorithms. Results. The results of theoretical and experimental studies of the systems of active shielding of the magnetic field generated by various overhead power lines inside a single and multi-storey building are presented. Originality. The possibility of reducing the induction of the initial magnetic field inside the shielded space to the level of sanitary standards is shown. Practical value. From the point of view of the practical implementation for a reasonable choice of the number and spatial arrangement of shielding windings of systems for active shielding of the magnetic field generated by various overhead power lines inside residential buildings of different storey’s are given.

Розглянуто зниження індукції магнітного поля до рівня сучасних санітарних норм за рахунок активного екранування в житлових будинках старої забудови, розташованих поблизу існуючих типових повітряних ліній електропередачі. Розглянуто активне екранування магнітного поля всередині одноповерхового і багатоповерхового будинку. При проектуванні визначалися кількість, конфігурація, просторове розташування екрануючих обмоток, а також струми в екрануючих обмотках. Методологія. Завдання проектування системи активного екранування зводиться до вирішення задачі мінімаксної векторної оптимізації. Вектор цільової функції в цій мінімаксній задачі обчислюється на основі закону Біо-Савара. Вирішення цієї проблеми грунтується на алгоритмах багатоагентної оптимізації. Результати. Представлені результати теоретичних і експериментальних досліджень систем активного екранування магнітного поля, що створюється різними повітряними лініями електропередачі всередині одно- і багатоповерхового будинку. Оригінальність. Показана можливість зниження індукціїпочаткового магнітного поля всередині простору, що екранується, до рівня санітарних норм. Практична цінність. З точки зору практичної реалізації представлені рекомендаці для обгрунтованого вибору кількості і просторового розташування екрануючих обмоток систем активного екранування магнітного поля, що створюється різними повітряними лініями електропередач всередині житлових будинків різноїповерховості.
Зниження рівня магнітного поля в житлових старих будівлях від ЛЕП засобів активного скринінгу
Keywords: overhead power line; magnetic field; system of active screening; повітряна лінія електропередачі; магнітне поле; система активного екранування